Comparison of Dynamics of Extracellular Accesses to the β(1) and β(2) Adrenoceptors Binding Sites Uncovers the Potential of Kinetic Basis of Antagonist Selectivity - Selvam, Balaji (2012)
From the molecular mechanism of antagonist unbinding in the β(1) and β(2) adrenoceptors investigated by steered molecular dynamics, we attempt to provide further possibilities of ligand subtype and subspecies selectivity. We have simulated unbinding of β(1)-selective Esmolol and β(2)-selective ICI-118551 from both receptors to the extracellular environment and found distinct molecular features of unbinding. By calculating work profiles, we show different preference in antagonist unbinding pathways between the receptors, in particular, perpendicular to the membrane pathway is favourable in the β(1) adrenoceptor, whereas the lateral pathway involving helices 5, 6 and 7 is preferable in the β(2) adrenoceptor. The estimated free energy change of unbinding based on the preferable pathway correlates with the experimental ligand selectivity. We then show that the non-conserved K347 (6.58) appears to facilitate in guiding Esmolol to the extracellular surface via hydrogen bonds in the β(1) adrenoceptor. In contrast, hydrophobic and aromatic interactions dominate in driving ICI-118551 through the easiest pathway in the β(2) adrenoceptor. We show how our study can stimulate design of selective antagonists and discuss other possible molecular reasons of ligand selectivity, involving sequential binding of agonists and glycosylation of the receptor extracellular surface.